pegegog 2022
DOI: 10.47750/pegegog.12.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive fusion on counselor performance : A comparative study of the experienced and novice counselor

Abstract: The counselor's internal competence has an impact on the counselor's self-management, primarily the cognitive domain. Failure to manage thoughts will cause cognitive distortions, even to identify biases in mental experiences. This condition is cognitive fusion. Cognitive fusion causes the counselor to be trapped in his mind, unable to discern the effects of his mind's external assumptions on conditions. The experienced counselor can predict the counselor's cognitive fusion condition. This study aims to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…Previous research found that implementing behavioral counseling and reframing techniques could lose negative thoughts toward training and social life (Hanafi et al, 2022;MacGill, 2018). The reframing technique could improve the cognitive bias of the intervention group than the control group.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous research found that implementing behavioral counseling and reframing techniques could lose negative thoughts toward training and social life (Hanafi et al, 2022;MacGill, 2018). The reframing technique could improve the cognitive bias of the intervention group than the control group.…”
Section: Discussionmentioning
confidence: 91%
“…This interpreting skill can occur since the reframing technique facilitates individuals to develop ways to manage their perceptions of a phenomenon, behavior, and interpretation of something (Weeks & D'Aniello, 2017). The uniqueness of the reframing technique in cognitive behavior counseling is effective in explaining the correlation among cognitive, occurrence, and psychomotor aspects of the counselee (Hanafi et al, 2022;Hidayah et al, 2017Hidayah et al, , 2018. Thus, they can reframe the events and participants during the event.…”
Section: Cognitive Behavior Counseling For Forgivingmentioning
confidence: 99%
“…This is a process that accommodates the growth of critical analytical thinking skills in students (Reed, 1998). Meanwhile, based on the study by Hanafi, Hidayah, Atmoko, Ramli, and Triyono (2022), the use of real problems in learning activities can stimulate students to be more motivated in understanding the concepts of the problems discussed in the learning process. Furthermore, real problems can also accommodate the learning process where students make reasoned decisions and defend them (Grasha, 1996).…”
Section: The Results Of Real-life Problem Effectiveness To Increase C...mentioning
confidence: 99%
“…Thus, it can increase the chances of success and effectiveness of the online counseling process. On other hand, barriers in online communication settings can impact the counselee's understanding of plans, monitoring counselors to unpredictable conditions [52]. The counselor's realistic expectations will give the counselor a more precise and realistic picture and predict the conditions [53].…”
Section: Description Of Every Mind Skills Levelmentioning
confidence: 99%